English Teaching and Learning in a Korean University Perceptions of International Professors - Han, Sang-Ho (Widya Mandala Catholic University Surabaya, 2020)
The purpose of this study is to investigate the perceptions of international faculty towards English teaching at a local university in South Korea. For data collection, a comprehensive survey questionnaire was administered to 71 international faculty teaching English at the same university. The survey consisted of items of questions concerning facultyâ€™s second language learning experience, teaching/learning philosophy, and teaching techniques and skills. Description of the responses revealed the following results: 1) Second language learning experience of faculty helps improving quality of instruction through understanding studentsâ€™ learning difficulties; 2) Facultyâ€™s view of language was mostly holistic while that of language learning was inclusive of different perspectives; 3) The role teachers was mainly that of a facilitator in a student-focused class; 4) For those applying CLT, it was used to engage students within a student-centered classroom; 5) A general maxim of teaching was the golden rule: â€œDo unto others, as you would have done unto you.â€; 6) Views on teaching explicit knowledge varied widely among faculty; 7) The majority of faculty chose to correct both global and local errors; 8) A number of strategies were utilized in order to help students overcome reluctance to speak such as letting students decide on what they want to learn and helping them realize it is okay to make mistakes; 9) In order to enhance studentsâ€™ communicative abilities, an innovation for general English education programs was suggested.